Estimation of Radiated Fields of Small Horizontal Submodules Based on a Lumped-Element Model - Valek, Martin; Leone, Marco (Radioengineering Society, 2006)
A novel approach to the estimation of radiated electric field of small horizontal submodules is presented. The principle idea is to describe the radiating submodule-on-motherboard structure with a lumped-element equivalent circuit which includes both the geometrical and the electrical parameters. The electromagnetic emission from the structure is approximated by the radiation characteristics of a Hertzian dipole driven by the antenna voltage resulting from the connector equivalent circuit. Therefore, no time consuming numerical field simulations are needed to evaluate the radiated electric field. Instead, a fast frequency circuit analysis with e.g. PSPICE is sufficient. Moreover, this modeling approach provides a clear insight concerning the influence of geometrical and electrical parameters with respect to radiated emissions. Finally, the computational solutions are compared with experimental results, demonstrating a good correspondence regarding engineering purposes.
Keywords: EMI of submodules; radiated emissions; lumped-element model; connector equivalent circuit; PSPICE analysis